Computer aided design : a conceptual approach - Sarkar, Jayanta (CRC Press, 2014)
IntroductionCAD System ToolsCAD LibrariesApplication-Oriented CAD SystemsAdvantages of CADIntroductionAdvantagesStructure of Computer-Aided Design ModelingIntroductionWindow IdentificationUnit SettingsSketch Entities, Objects, and ClassificationDatumsSketch Entities3-D CurvesSurfacesSolidsRegional OperationsSketching OperationsUse of Model Tree and Sequence of OperationAccessing of CAD LibrariesCurve EntitiesIntroductionCurvesLinesCirclesEllipsesParabolasHyperbolasConicsCubic SplinesBezier CurvesB-Spline CurvesProject WorkSketchingIntroductionSketching ToolsModification ToolsAnnotation ToolsAd.